Brazilian research about prevention of cervical neoplasia: an integrative review - Jaqueline Apolônio de Freitas Guimarães; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro; Juliane Girão de Moura (Rev Rene)
This is an integrative review that aimed to synthesize the scientific knowledge published in national nursing journals about the prevention of cervical cancer. It was made a literature review in May 2009 in BIREME, covering the national nursing publications, from 1999 to 2009. We identified 15 articles that comprised the study sample. Of these, 11 addressed the nursing care, 6 were about prevention of cancer and 5 were about risk factors for such disease. In 4 articles the studies were accomplished in the Family Health Care Unit (UBASF) which was the most prevalent place. It was found out that 6 of the articles used the qualitative method. The most studied population was formed by users of the Family Health Care Unit, in 3 studies. It was so concluded that the national research about this topic was related to the problems identified in health places, either in the effectiveness of the examination, in the knowledge of users or in conducted health education.